1989
DOI: 10.1093/bja/62.4.368
|View full text |Cite
|
Sign up to set email alerts
|

Extradural Pressure Following the Injection of Two Volumes of Bupivacaine

Abstract: We investigated the influence of the pressure generated by low lumbar extradural injection of bupivacaine on the development of block in a randomized double-blind study. Thirty patients (aged 17-66 yr) received one of two volumes of 0.75% bupivacaine. Group I (n = 15) received 10 ml (75 mg) and group II (n = 15) 15 ml (112.5 mg). Injection of the larger volume resulted in a greater pressure at the end of injection, but within 1 min this decayed to the same plateau pressure that was produced by the smaller volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
1
2

Year Published

1993
1993
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 9 publications
2
22
1
2
Order By: Relevance
“…Park et aL s also reported that there were only small differences in spread with 10, 15, 20 ml lidocaine. In addition, no correlation between the volume and the effect was reported by Duggan et trL 1 or Paul et al 2 Our finding of no difference in cold sensation block among three groups was consistent with these reports. The relationship between epidural saline and spread of the subsequent anaesthetic has been reported by Iwama 6 who showed that a larger volume of saline using LOR caused a greater extent of hypaesthesia.…”
Section: Discussionsupporting
confidence: 91%
“…Park et aL s also reported that there were only small differences in spread with 10, 15, 20 ml lidocaine. In addition, no correlation between the volume and the effect was reported by Duggan et trL 1 or Paul et al 2 Our finding of no difference in cold sensation block among three groups was consistent with these reports. The relationship between epidural saline and spread of the subsequent anaesthetic has been reported by Iwama 6 who showed that a larger volume of saline using LOR caused a greater extent of hypaesthesia.…”
Section: Discussionsupporting
confidence: 91%
“…There were no differences in age, height or weight among the two groups (Table). The number of spinal segments with hypesthesia to cold in the i ml, 5 rnl and 10 ml saline groups in the mepivacaine 1% group were 12.5 [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] (Figure 2). The number of segments with hypesthesia for coldness in the 5 ml and 10 ml saline groups in the 1.5 % mepivacaine group was greater than that in the 1 ml saline group (P< 0.05) (Figure 2).…”
Section: Result~mentioning
confidence: 99%
“…Fifteen minutes after the injection of I0 ml mepivacaine, the dermatome levels of hypesthesia to cold and pinprick were determined by an individual blinded to the saline volume. ~tdts: The number of spinal segments with hypesthesia to cold in the three subgroups in the mepivacaine 1% group were 12.5 [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] .5], respectively. Saline volume did not alter the anesthetic level of the mepivacaine 1%, although it did affect the anesthetic spread of the mepivacaine 1.5%.…”
mentioning
confidence: 99%
See 2 more Smart Citations